2022
DOI: 10.1002/jmv.28250
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox viral detection in semen specimens of confirmed cases: A systematic review and meta‐analysis

Abstract: Background The current literature shows increasing concerns about potential seminal transmission of monkeypox virus (MPV). Accordingly, we aimed to understand better the potential presence of MPV in the seminal uids and others specimens obtained from monkeypox (MPX) cases.Methods On June 26, 2022, a systematic search of the literature was conducted across PubMed, Scopus, Web of Science, EMBASE, ScienceDirect, ProQuest, EBSCOHost-Academic Search Complete, and Google Scholar to nd articles that examine the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
(154 reference statements)
1
28
0
1
Order By: Relevance
“…The largest number of cases registered with co-infection of Mpox and HIV are male (91.44%), which is consistent with other reviews in which it is reported that the population most affected by Mpox are men [ 6 , 68 , 69 , 70 ]. The prevalence of Mpox and HIV co-infection was 40% of the cases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The largest number of cases registered with co-infection of Mpox and HIV are male (91.44%), which is consistent with other reviews in which it is reported that the population most affected by Mpox are men [ 6 , 68 , 69 , 70 ]. The prevalence of Mpox and HIV co-infection was 40% of the cases.…”
Section: Discussionsupporting
confidence: 89%
“…This disparity would suggest that transmissibility could be higher in people with HIV [ 74 ]. Mpox can be transmitted by respiratory secretions, skin lesions, contaminated fomites and through seminal fluid [ 69 , 75 ]. Reda et al [ 69 ] found that seminal fluid from Mpox-infected patients had a high Monkeypox virus DNA positivity rate (72.4%), behind the positivity rate of anogenital/rectal lesion samples (74.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MPXV has been detected in the semen of infected men, which could plausibly transmit the infection [ 21 ]. Reda A et al reported in their systematic review and meta-analysis study that MPXV is highly prevalent in seminal samples of MPX cases, further corroborating the role of sexual transmission of the disease [ 95 ].…”
Section: Discussionmentioning
confidence: 89%
“…The available literatures showed increasing concerns about possible seminal transmission of MPXV ( Hornuss et al, 2022 ; Lapa et al, 2022 ; Noe et al, 2022 ; Peiró-Mestres et al, 2022 ; Raccagni et al, 2022 ; Reda et al, 2022 ; Reda et al, 2023 ). Detection of viruses in the testes is commonly secondary to viraemia because the blood–testis barrier may be liable to viruses, especially when systemic or local inflammation occurs.…”
Section: Possible Seminal Transmission Of Mpxvmentioning
confidence: 99%